High power broad-area lasers with buried implantation for current confinement. (9th September 2019) - Della Casa, P; Martin, D; Maaßdorf, A; Adam, T; Thies, A; Beier, M; Häusler, K; Knigge, A; Weyers, M
Abstract: Broad area lasers emitting near 915 nm are fabricated using a 2-step epitaxial growth process, with an intermediate implantation of silicon or oxygen ions. This approach allows for the introduction of buried lateral current confinement layers at moderate cost in terms of process complexity. The effectiveness of this strategy with respect to different implantation conditions is tested, obtaining up to ≈12% reduction of threshold current and ≈15% increase of slope efficiency with respect to standard lasers. Also a significant improvement of the beam quality-which is relevant to coupling efficiency-has been obtained in terms of reduction of the lateral beam product parameter, from 3.8 mm × mrad at 5A for standard lasers to 2.2 mm × mrad for implanted and regrown lasers, but at the expense of energy efficiency.